Dialogue between the formal and the informal sector in open innovations at the grassroots' level. Issue 1 (9th February 2015) - Masudul Alam Choudhury, Professor; Saxena, Stuti
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Whereas a lot of emphasis has been placed on the open innovations (Chesbrough, 2003, von Hippel, 2005) and their implications in the formal sector, this paper purports to fill the literature gap in identifying the process of dialogue between the formal and the informal sector with reference to the open innovations, emanating at the grassroots' level, for effecting inclusive and a sustainable development. This causality is being sought to be achieved through initiation, accessibility, building-the-bridges and finding unique solutions to the problems through mutual dialogue and reciprocity. Thus, this interplay of interaction shall facilitate the shaping up of sustainable and inclusive development through the open innovations. It may be pertinent to note here that the present paper shall specifically limit its scope to the conceptualization for such a dialogue to eventually happen in due course of time. Design/methodology/approach – Theoretical build-up. Findings – For harnessing the potential of the innovations at the grassroots, it is important that bridges be built between the informal and the formal spaces. Originality/value – Hitherto, the notion of inclusive and sustainable development was not studied in the research with respect to the open innovations at the grassroots (informal sector). The paper is attempt at filling this gap.